Proposal of minimum elements for screening and diagnosis of gastric cancer by an international Delphi consensus. Issue 1 (24th February 2022) - Kakushima, Naomi; Fujishiro, Mitsuhiro; Chan, Shannon Melissa; Cortas, George Adel; Dinis‐Ribeiro, Mario; Gonzalez, Robinson; Kodashima, Shinya; Lee, Sun‐Young; Linghu, Enqiang; Mabe, Katsuhiro; Pan, Wensheng; Parra‐Blanco, Adolfo; et al.
Abstract: The World Endoscopy Organization Stomach and Duodenal Diseases Committee extracted minimum elements for screening and diagnosis of gastric cancer (GC) in aim to support countries that do not have national guidelines on screening and diagnosis of GC. Current national or international guidelines were collected worldwide and recommendations were classified according to the quality of evidence and were finalized through a modified Delphi method. The minimum elements consist of seven categories: [1] Extraction of high‐risk patients of GC before esophagogastroduodenoscopy (EGD), [2] Patients who need surveillance of GC, [3] Method to ensure quality of EGD for detection of GC, [4] Individual GC risk assessment by EGD, [5] Extraction of high‐risk patients of GC after EGD [6] Qualitative or differential diagnosis of GC by EGD, and [7] Endoscopic assessment to choose the therapeutic strategy for GC. These minimum elements will be a guide to promote the elimination of GC among countries with a high incidence of GC who lack national guidelines or screening programs.